Identification of Cadalene-β-Carboxylic Acid from Barks of Bawang Hutan (Scorodocarpus borneensis Becc.) - Kartika, Rudi; Bustanussalam, Bustanussalam; Farida, Farida; Simanjuntak, Partomuan (Annales Bogorienses, 2012)
One sesquiterpene compound has isolated and identified from ethylacetate extract of bawang hutan (Scorodocarpus borneensis Becc.) barks. The barks were macerated with methanol, and then partitioned with mixture of ethylacetate-water (1:1). Fractionation of the ethylacetate phase by column chromatography gave pure compound. Based on data interpretation from of ultra-violet (UV) spectra, Fourier Transform Infra Red (FT-IR), NMR 1D (1H and 13C-NMR); NMR 2D (HMQC, COSY, HMBC) and comparison with literature, the pure isolated compound was determined as a sesquiterpene compound, cadalene-β-carboxylic acid which exhibit LC50 of 42.32 ppm.